Serpiginous Choroiditis Presenting in Association With Clostridium difficile Infection and Ulcerative Colitis. (March 2021) - Pollmann, André S.; Mishra, Amit V.; Betsch, Devin M.; Francisconi, Carolina L. M.
Purpose: This work reports a case of serpiginous choroiditis (SC) in association with ulcerative colitis and Clostridium difficile infection. Methods: A case report is discussed. Results: A 35-year-old man with a history of ulcerative colitis and recently treated C difficile infection presented with a rapid decline in central visual acuity in both eyes. Examination findings included geographic creamy-white lesions extending from the peripapillary region in both eyes. Multimodal imaging and negative infectious workup results supported the diagnosis of SC. Visual acuity and examination findings improved after initiation of systemic prednisone therapy. Adalimumab was initiated as a steroid-sparing treatment. At the last follow-up, 5 months after the initial presentation, SC and ulcerative colitis both remain in remission. Conclusions: SC has been previously described in patients with systemic disorders, including autoimmune conditions. This patient developed SC following C difficile infection and in the context of active ulcerative colitis. To our knowledge, this is the first report of SC in association with these entities.